Hubungan Pengetahuan Ibu dan Riwayat Pemberian ASI Eksklusif dengan Kejadian Stunting pada Anak Usia 24-59 Bulan - Desriani, Fithri; syahda, syukrianti; lasepa, wanda (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Stunting is slow growth, namely the height of toddlers is not in accordance with age caused by various factors, including lack of knowledge of mothers and toddlers not exclusively breastfeeding. The prevalence of stunting in Indonesia is 21.6%, in Riau 17.0% and in Pekanbaru City 16.8% in 2022. The purpose of this study was to analyze the relationship between maternal knowledge and history of exclusive breastfeeding with the incidence of stunting. Type of quantitative research with case control design. Population: 28 mothers under five are stunted and 28 mothers under five are not stunted. The study will be conducted from May 30 to June 16, 2023. Collection of maternal knowledge data and exclusive breastfeeding history using questionnaires, nutritional status data anthropometric measurements of height. Data analysis used univariate and bivariate analysis with chi square. The results of the univariate analysis of 28 stunting toddlers, 15 respondents (53.6%) had good knowledge, of 28 non-stunting toddlers, 19 respondents (67.9%) had good knowledge. The results of the univariate analysis of the history of exclusive breastfeeding in 28 stunted toddlers, 23 toddlers (82.1%) were not exclusively breastfed, of 28 toddlers who were not stunted, 18 toddlers (64.3%) who were not exclusively breastfed. Chi square results showed no relationship between maternal knowledge (p-value = 0.274) and history of exclusive breastfeeding (p-value = 0.217) with the incidence of stunting. Conclusion There is no significant relationship between maternal knowledge and history of exclusive breastfeeding with the incidence of stunting in children aged 24-59 months in the working area of the Puskesmas Limapuluh Kota Pekanbaru. Mothers are expected to actively participate in posyandu activities, to find out the growth of children.